2018
DOI: 10.1111/jai.13701
|View full text |Cite
|
Sign up to set email alerts
|

Potential responses of the Lower Missouri River Shovelnose Sturgeon (Scaphirhynchus platorynchus) population to a commercial fishing ban

Abstract: Summary We developed an age‐structured population matrix model to perform population viability analysis for Lower Missouri River (LMR) shovelnose sturgeon (Scaphirhynchus platorynchus). We investigated potential effects of the commercial fishing moratorium put in place to help protect the similar‐appearing pallid sturgeon (S. albus). The model applies different components of total variance in life history parameters at different levels: sampling variance (parameter uncertainty) between model iterations; tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We structured chub population models based on hierarchical stochastic fish population models developed by Wildhaber et al () and Green, Wildhaber, and Albers (). Age‐structured female‐only models were constructed because ϕ 0‐4 were available and males were assumed to not limit λ .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We structured chub population models based on hierarchical stochastic fish population models developed by Wildhaber et al () and Green, Wildhaber, and Albers (). Age‐structured female‐only models were constructed because ϕ 0‐4 were available and males were assumed to not limit λ .…”
Section: Methodsmentioning
confidence: 99%
“…For categorical life history characteristics such as age at first spawn and spawn frequency, we tested multiple levels (see below). As done by Wildhaber et al () and Green et al (), we increased or decreased mean values for length‐at‐age and fecundity‐at‐length directly rather than individual von Bertalanffy growth model terms because preliminary tests showed that when individual terms were varied independently the population model would draw unrealistic values of length or fecundity. We assessed influence of ϕ changes to each age class by running the model with each age specific ϕ set individually to 1, other ϕ s unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…The research from the current study contributes additional, more specific details of how food and habitat availability and substrate selection of these sympatric fish groups in the lower Missouri River may influence patterns of viability in their populations suggested by previous research (Bajer and Wildhaber 2007;Wildhaber et al 2007Wildhaber et al , 2011Wildhaber et al , 2017aWildhaber et al , 2017bAlbers et al 2018;Green et al 2018). The research results from the current study provide information on the potential effects of lack of light and food delivery on substrate selection of early juvenile Pallid Sturgeon, Shovelnose Sturgeon, and hybrid sturgeons and adult Shoal Chub and Sicklefin Chub.…”
Section: Sourcementioning
confidence: 65%
“…2017a, 2017b; Green et al. 2018). This is especially true through the early juvenile stage (i.e., exogenously feeding larvae to age‐1 or age‐0 juveniles).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation